P77 L1CAM is an independent predictor of poor survival of endometrial cancer undergoing full lymphadenectomy and adjuvant chemotherapy. (1st November 2019) - Oku, A; Asano, H; Hatanaka, KC; Matsuoka, R; Kato, T; Konno, Y; Mitamura, T; Ihira, K; Nozaki, A; Takeda, M; Kobayashi, N; Kudo, M; et al.
Abstract : Introduction/Background: L1 cell adhesion molecule (L1CAM), a transmembrane protein of the immunoglobulin family that has been implicated in promoting cancer cell proliferation, invasion, migration, and metastasis, has been established as an important predictor of poor survival of early-stage endometrial cancer patients. We aimed to investigate whether L1CAM remains significant predictor of poor survival of the patients with endometrial cancer undergoing extensive surgical staging and adjuvant chemotherapy in this retrospective analysis. Methodology: We prepared tissue microarray (TMA) from surgical tissue specimens of 185 endometrial cancer patients who underwent full lymphadenectomy combined with adjuvant chemotherapy for patients at risk for recurrence, and evaluated expression of L1CAM by immunohistochemistry (IHC). L1CAM positivity was correlated with clinicopathological factors and its prognostic significance was investigated by multivariate analysis using Cox regression model. Results: Among 169 cases with over three years of follow-up period (median 95 months, 5–186 months), 53 cases (31.4%) showed positivity of L1CAM. L1CAM positivity was significantly correlated with non-endometrioid histology (p<0.0001), carcinosarcoma (p=0.0008), positive cytology (p=0.005), and p53 positivity (p<0.0001). L1CAM positive patients showed higher recurrent rate(15/53 (28.30%) vs 16/116 (13.79%), p=0.0277) and frequency of distant failure (11/14 (78.57%) vs 5/16 (31.25%), p=0.0361) than L1CAM negative patients. L1CAM positivity was a significant predictor of poor survival among advanced-stage patients (5-year OS; 49.0% vs 87.8%, p=0.0008, PFS; 35.7% vs 75.6%, p=0.0026), but not early-stage patients (5-year OS; 100% vs 98.7%, p=0.3456, PFS; 83.2% vs 93.3% p=0.2112). Multivariate analysis revealed that surgical stage and L1CAM positivity were independent predictors of poor survival. OS can be stratified into three groups by the combination of stage and L1CAM positivity. Conclusion: L1CAM is an independent predictor of poor survival of Japanese patients with advanced-stage endometrial cancer undergoing full lymphadenectomy and adjuvant chemotherapy. New treatment strategy should be developed for L1CAM positive patients with endometrial cancer. Disclosure: Nothing to disclose.